Synthesis, characterization, and thermoelectric properties of superconducting (BEDT-TTF)2I3 nanoparticles. Issue 31 (21st July 2016) - Chtioui-Gay, I.; Faulmann, C.; de Caro, D.; Jacob, K.; Valade, L.; de Caro, P.; Fraxedas, J.; Ballesteros, B.; Steven, E.; Choi, E. S.; Lee, M.; Benjamin, S. M.; et al.
Abstract : (BEDT-TTF)2 I3 nanoparticles of 2–6 nm have been isolated, and they exhibit a superconducting behaviour and encouraging thermoelectric properties. Abstract : The synthesis of (BEDT-TTF)2 I3 in the presence of two neutral amphiphilic molecules [ N -octylfurfurylimine and 1-octanamine, N -(2-thienylmethylene)] leads to single and aggregated nanoparticles of 2 to 6 nm size. The samples contain highly crystalline nanoparticles of the βCO -(BEDT-TTF)2 I3 phase, confirmed by XRD. Temperature dependent resistance and magnetic susceptibility studies evidence the superconducting transition characteristics of the βCO -(BEDT-TTF)2 I3 phase. The I – V curve of a single nanoparticle aggregate, measured using AFM, exhibits an expected semiconductor-like behaviour. Thermoelectric studies led to a ZT of 1.47 × 10 −3 at 300 K.